Effect of transient thermal shocks on alcoholic fermentation performance - Vargas Trinidad, Andrea Susana; Lerena, María Cecilia; Alonso Del Real, Javier; Esteve Zarzoso, Braulio; Mercado, Laura Analia; Mas, A.; Querol, Amparo; Combina, Mariana (Elsevier, 2019)
Stuck and sluggish fermentations are among the main problems in winemaking industry leading to important economic losses. Several factors have been described as causes of stuck and sluggish fermentations, being exposure to extreme temperatures barely studied. The objective of this study was to identify thermal conditions leading to stuck and sluggish fermentations, focusing on the impact of an abrupt and transient decrease/increase of temperature on fermentation performance and yeast viability/vitality. Different strains of Saccharomyces cerevisiae, SBB11, T73, and PDM were evaluated in synthetic grape must fermentations. Cold shocks (9 °C and 1.5 °C for 16 h) carried out on different days during the fermentation process were unable to alter fermentation performance. Conversely, shock temperatures higher than 32 °C, applied in early stages of the process, lead to sluggish fermentation showing a delay directly related to the temperature increase. Fermentation delay was associated with a decrease in cell vitality. The impact of the heat shock on fermentation performance was different depending on the strain evaluated and nitrogen supplementation (with or without diammonium phosphate addition). None of the conditions evaluated produced a stuck fermentation and importantly, in all cases must nutrition improved fermentation performance after a heat shock.